Roman mirrors from a private collection in the Hungarian National Museum - Bózsa, Anikó (Dissertationes Archaeologicae, 2013)
In 2002, the Hungarian National Museum obtained by condemnation and adjudication a private metal collection from Kaposvár with more than 10,000 objects, among them numerous Roman mirror fragments. Unfortunately there is no information on the provenance of the finds, but it is possible that they have a south Pannonian origin. The aim of the present paper is the description and classification of the mirror fragments as well as their comparison to the Pannonian and Italian types and forms from other Roman provinces.